(untitled) (Revista Direitos Humanos e Democracia, 2026)
Since the turn of modernity, indigenous peoples have been constantly subjugated, so that their consideration as full subjects of Law is still questioned in many Latin American countries, making it extremely difficult for them to accept their traditions and worldviews. This situation facilitates the violation of their rights, especially due to the subalternity that surrounds them when it comes to claiming them. In view of this, this text has as its research problem the following question: based on the analysis of the participation of indigenous peoples in the Inter-American Human Rights System in demands against violations committed by the Brazilian State, how does Decolonial International Law contribute/could contribute to the understanding of indigenous peoples as subjects of international law? To answer the proposed question, we chose to use the dialectical method as a method of approach based on the qualitative understanding of the current structure of international law, which does not allow the effective participation of indigenous peoples in the construction of International Law, confronting it with the emergence of Decolonial International Law, which, through the intercultural dialogue and the consequent breaking of abyssal lines, ultimately sees indigenous peoples as subjects.